Evaluation of soil properties variability along a toposequence in Wasinmi, Southwest Nigeria - Oyebiyi Oluwatoyosi Oyetola; Fagbohun Usman Olaleke; Egbinola Oluwatosin Abimbola; Ojetade Julius Olayinka; Muda Sikiru Adekoya; Adewumi Opeyemi Ayomide (Agricultura Tropica et Subtropica)
Topography significantly influences soil development and characteristics within an uneven agricultural field. Therefore, a comprehensive understanding of soil attributes and processes through detailed pedological knowledge is crucial for effective soil management. This research was carried out in Wasinmi, southwestern Nigeria, to delineate and categorise the soils across different slopes for agricultural insights. Three soil profiles were excavated across the topographical sequence, specifically designated as upper, middle, and lower slope positions. The prevailing soil texture was sandy loam with a discernible trend of lighter soil colour as the slope descended and soil depth increased. The pH of the soil ranged from moderately acidic to slightly acidic. The saturated hydraulic conductivity and soil organic matter content were lowest on the lower slope. Available phosphorus distribution varied inconsistently with higher concentrations of heavy minerals observed at the upper slope. The study underscored the influential role of topography in soil property variations and the need for tailored management practices. The classification of the soils revealed Typic Plintustults in the upper and middle slope positions, while the soils in the lower slope were identified as Typic Kandiaquults. This study demonstrated that topography significantly influenced soil properties, thereby emphasising the need for informed practices to better support the long-term sustainability of land use and agricultural outputs in topographically diverse landscapes.